VD_FINDINFO HC / 2015 / 688 vom 30. Juni 2015 - VD Tribunal cantonal (2015)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, ENFANT, REVENU HYPOTHÉTIQUE | 176 al. 3 CC, 276 al. 1 CC, 276 al. 2 CC, 285 al. 1 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH)